2020
DOI: 10.1002/brb3.1674
|View full text |Cite
|
Sign up to set email alerts
|

Transient effects of multi‐infusion ketamine augmentation on treatment‐resistant depressive symptoms in patients with treatment‐resistant bipolar depression – An open‐label three‐week pilot study

Abstract: Introduction While the psychiatric benefits of ketamine have been verified through clinical trials, there is limited information about ketamine augmentation in patients with treatment‐resistant bipolar depression (TRBPD). Hence, in the present study, we investigate the therapeutic efficacy and functional brain alterations associated with multi‐infusion ketamine augmentation in patients with TRBPD. Methods The present three‐week study included 38 patients with TRBPD, all… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
18
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(20 citation statements)
references
References 91 publications
(156 reference statements)
2
18
0
Order By: Relevance
“…Although not statistically significant, this observation is in line with other reports. 34,35 In line with other studies, we observed an antisuicidal effect reflected by a decrease in the score of item 10 in MADRS. This effect is described in a meta-analysis of single-infusion studies of MDD.…”
Section: Discussionsupporting
confidence: 92%
“…Although not statistically significant, this observation is in line with other reports. 34,35 In line with other studies, we observed an antisuicidal effect reflected by a decrease in the score of item 10 in MADRS. This effect is described in a meta-analysis of single-infusion studies of MDD.…”
Section: Discussionsupporting
confidence: 92%
“… 35 This aligns more with the findings from Zhuo et al. 32 Baseline differences between patients and controls were also not replicated from Abdallah et al. 31 Although these are small effects in modest sized samples, the inconsistency may also result from scan timing post-ketamine, i.e.…”
Section: Functional Connectivitysupporting
confidence: 56%
“…Continuing the data-driven approach with treatment-resistant bipolar patients, Zhuo did not reveal a relationship between global functional connectivity and HAMD scores in response to ketamine. 32 Oddly in this study, many patients relapsed in the second week of treatment, and the average depression score was higher post-treatment. The authors cited that the atypical clinical findings may be a result of glutamate exhaustion due to multiple glutamate modulating medications.…”
Section: Functional Connectivitymentioning
confidence: 51%
See 1 more Smart Citation
“…This receptor is believed to be responsible for the psychotropic effects [5]. Another natural product like ketamine also can rapidly relieve depressive symptoms among depressed patients [25].…”
Section: Discussionmentioning
confidence: 99%